2011
DOI: 10.1101/lm.2213711
|View full text |Cite
|
Sign up to set email alerts
|

Working memory deficits, increased anxiety-like traits, and seizure susceptibility in BDNF overexpressing mice

Abstract: BDNF regulates components of cognitive processes and has been implicated in psychiatric disorders. Here we report that genetic overexpression of the BDNF mature isoform (BDNF-tg) in female mice impaired working memory functions while sparing components of fear conditioning. BDNF-tg mice also displayed reduced breeding efficiency, higher anxiety-like scores, high self-grooming, impaired prepulse inhibition, and higher susceptibility to seizures when placed in a new empty cage, as compared with wild-type (WT) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 88 publications
9
60
1
1
Order By: Relevance
“…They also show altered anxiety phenotypes (Skelton et al, 2003), whereas its human ortholog PTPRA resides in the 20p13 region which has repeatedly been linked to psychosis (Fanous et al, 2008, Teltsh et al, 2008). As already suggested in the literature (Audet, Goulet, 2006, Isingrini et al, 2011, Papaleo et al, 2011), grooming responses in mice may represent traits highly relevant to schizophrenia, anxiety and depression, and our results are in line with this notion.…”
Section: Discussionsupporting
confidence: 93%
“…They also show altered anxiety phenotypes (Skelton et al, 2003), whereas its human ortholog PTPRA resides in the 20p13 region which has repeatedly been linked to psychosis (Fanous et al, 2008, Teltsh et al, 2008). As already suggested in the literature (Audet, Goulet, 2006, Isingrini et al, 2011, Papaleo et al, 2011), grooming responses in mice may represent traits highly relevant to schizophrenia, anxiety and depression, and our results are in line with this notion.…”
Section: Discussionsupporting
confidence: 93%
“…A global increase in BDNF could, in principle, cause more harm than good. Indeed, overexpression of BDNF has been reported to increase anxiety-like behavior, seizure activity, and impair some forms of memory (Croll et al 1999;Govindarajan et al 2006;Cunha et al 2009;Papaleo et al 2011). …”
Section: Resultsmentioning
confidence: 99%
“…14 Papaleo et al, 2011). From literature data it seem that BDNF and TrkB are important for antidepressant drug action however their role in development of depressive like symptoms remains uncertain (for review see Lindholm and Castren, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Moreover it has been shown that mice with forebrain overexpression of BDNF show gender differences in depressive-like behavior and can cause working memory impairments. Specifically males overexpressing BDNF has been shown to exhibit antidepressant-like effect in Porsolt Swim Test (Govindarajan et al, 2006) while females did not (Papaleo et al, 2011). Furthermore females overexpressing BDNF displayed impaired working memory and both sexes exhibited increased anxiety (Govindarajan et al, 2006, A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 98%